THE CENTRAL STYLE OF AZERI FOLKSONGS - JÁNOS SIPOS (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
To what use does comparative ethnomusicological research over a vast area be put? It suffices for a nation to realize that it is imperative to know the music of its neighbors and language relatives in order to explore the particular and general features of its own folk music. It holds true in general, too, that a comparative examination is more informative and revelatory than the separate study of the music of the peoples concerned. Comparative musicology also leads to more universal findings, illuminating fundamental human characteristics. „Indeed, all the world’s tribes, peoples, and races have lived in continuous intercourse since the very beginning of history; they have met in marriage, trade, and war. In this process of exchange and merger, they discard their weapons, tools, and implements for better ones. But they preserve their ancient songs; for singing, an expression of man’s soul and motor impulse, has little to do with the mutable surface of life, and nothing with the struggle for existence. This is why music is one of the steadiest elements in the evolution of mankind.” (Sachs 1943: 21) To spin on this thought: it is intriguing to determine the basic musical types of a large geographical-cultural expanse. It is also important to know what specific manifestations of these basic forms predominate in the music of various people or geographical areas.